Penentuan Strategi Pemasaran pada Cafe Herdacake Puger Menggunakan Analisis SWOT - Adi Laksono; M Naely Azhad; Tatit Diansari Reskiputri (BUDGETING : Journal of Business, Management and Accounting, 2023)
Currently, one of the business competitions occurs very tightly in businesses engaged in the culinary field. This is due to the rapid development of business in the culinary field of cafes in various cities including in Jember City. Some people choose to be in the culinary field because the business is considered the most profitable. The development of the Cafe business in Jember City, Puger Village, is marked by the increasing number of competitors in the same business. HerdaCake which is located in Kerajan Hamlet, Puger Kulon Village, Puger Jember District. Jember City is one of the business ventures in the culinary field of Cafe with a modern and instagramabel, kidsfriendly and comfortable feel. Various strategies have been applied to HerdaCake to be able to grab and attract the attention of customers and be able to keep up with the fierce competition. The purpose of this study was to determine the marketing strategy of Café Herdacake using a SWOT analysis. Based on the results of the SWOT analysis, it shows that Café Herdacake is positioned by the Herdacake café, which is in the square V marked astrix (2.82; 2.60) in quadrant V, this means that the Herdacake café should apply a Stability or Growth strategy which is a growth strategy through expansion and expanding the area of marketing and product sales or it can be product dissertation. This strategy can be applied by market penetration and market development. Keywords: Cafe, Marketing Strategy, SWOT Analysis